A Study of Logistics Costs Using Activity-Based Cost Analysis Techniques: A Case Study of Dwarf Napier Grass Growers - Taengphukieo, Ratchada; Donprasert, Krissana; Samransom, Narisara (Frontiers in Engineering Innovation Research, 2020)
The objective of this research was to study the cost of logistics by applying the activity based cost analysis technique. A case study of dwarf napier grass group of farmers at Ban Din Din Daeng, Muang District, Kalasin Province, data were collected by using questionnaires and in-depth interviews, 30 samples of dwarf Napier grass were interviewed and the data were analyzed by activity based costs. Technique found that the main activities in the operation of the dwarf napier grass growers consist of 5 main activities which are 1. Plantation preparation activity 2. Planting activity 3. Maintenance activity 4. Harvesting and 5. Transportation activity. The overall activity based cost was 2,059,500 baht per year. The main activitiy with the highest cost are planting activity the total cost is 686,700 baht per year or 33.34 percent, Followed by transportation. With a total cost of 576,000 baht per year, representing 27.97 percent. While, ranking was harvesting activity with a total cost of 398,400 baht per year or 19.34 percent.